2017
DOI: 10.24326/asphc.2017.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Phenolic Compounds of Four Aromatic Lamiaceae Species in Consequence of Different Water Supply

Abstract: The reactions of lemon balm, marjoram, peppermint, thyme were investigated and compared in a pot experiment, adjusting 70% and 40% of soil water capacity (SWC). Biomass, total phenolic content (TPC), rosmarinic acid content (RA) and antioxidant capacity (FRAP, DPPH) of both the shoots and roots were measured. As an universal phenomenon the water stress (40% SWC) decreased the total biomass production of all species drastically. The highest increase was observed in the shoot mass of peppermint and lemon balm (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…The effect of a water shortage on the elevation of the RA content is more pronounced in warmer conditions. Previous studies demonstrated variable results regarding this topic (Németh-Zámbori et al, 2017). A short-term heat treatment (38°C for 5 h) elevated the RA content of Melissa officinalis L. (Pistelli et al, 2019).…”
Section: Conflict Of Interestmentioning
confidence: 97%
See 2 more Smart Citations
“…The effect of a water shortage on the elevation of the RA content is more pronounced in warmer conditions. Previous studies demonstrated variable results regarding this topic (Németh-Zámbori et al, 2017). A short-term heat treatment (38°C for 5 h) elevated the RA content of Melissa officinalis L. (Pistelli et al, 2019).…”
Section: Conflict Of Interestmentioning
confidence: 97%
“…Lamiaceae species react due to a significant elevation of the RA content stemming from a lack of water (Manukyan, 2011;Németh-Zámbori et al, 2017). The effects of a water shortage on RAS gene expression and RA content outcomes in intact Thymus vulgaris plants have not yet been studied.…”
Section: Changes Of Ras Expression Levels and Ra Contents Due To Envi...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that dry conditions stimulate their production. According to several reports, the total phenolic content (TPC) of peppermint samples seems to increase significantly in stressed plants [ 11 , 12 , 14 , 15 ]. Moreover, the ratio of the major phenolic compounds seems to increase remarkably, (such as rosmarinic acid and rutin compounds) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%